FINANCIAL DISTRESS PREDICTION MODEL IN TOBACCO SUB-SECTOR COMPANIES - Nurul Chalijah Rangkuti; Idzni Syafitri; Didik Gunawan; Willy Cahyadi (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
The tobacco industry in Indonesia faces various challenges, such as increasing tobacco excise rates, inflation, declining purchasing power, and changes in consumer behavior towards alternative tobacco products. These conditions have the potential to affect company financial performance and increase the risk of financial distress . This study aims to predict financial distress conditions in tobacco sub-sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period using the Altm an Z-Score, Zmijewski X-Score, Springate S-Score, and Grover G-Score models. This study uses a quantitative descriptive method with secondary data obtained from annual financial reports. The study population consists of all tobacco sub-sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period, namely four companies, which were also used as research samples using a saturated sampling technique. The results show that PT Gudang Garam Tbk, PT HM Sampoerna Tbk, and PT Wismilak Inti Makmur Tbk are consistently in the healthy category based on all prediction models used. Meanwhile, PT Indonesian Tobacco Tbk exhibits a higher level of financial vulnerability, falling into the grey area category based on the Altman Z-Score model and experiencing financial distress based on the Springate S-Score model. This research contributes to providing a comparative overview of the use of four financial distress prediction models in the tobacco subsector as a basis for decision-making by management, investors, and creditors. Overall, the financial condition of tobacco subsector companies during the 2020–2024 period remains relatively stable.